The effects of co-designed physical activity interventions in older adults: A systematic review and meta-analysis. - Amanda Zacharuk; Alison Ferguson; Chelsea Komar; Nicole Bentley; Alexandra Dempsey; Michelle Louwagie; Sachi O'Hoski; Cassandra D'Amore; Marla Beauchamp (PLoS ONE)
Background Physical activity (PA) declines with age despite the knowledge that physical inactivity is a leading cause of disease, death, and disability worldwide. To better tailor PA interventions to older adults, researchers are turning to the collaborative principles of co-design. The purpose of this systematic review was to compare the effectiveness of co-designed PA interventions and standard care for increasing PA and other health outcomes (i.e., physical function, quality of life, mental health, functional independence, attendance and attrition rates) in older adults. Methods A search was conducted in MEDLINE, AgeLine, CINAHL, Embase, and SPORTDiscus. Records were screened by independent pairs of reviewers. Primary research studies conducted among community-dwelling older adults (age 60+) comparing co-designed PA interventions to standard care were considered for inclusion. Controls included wait-list control, usual care, sham interventions, PA interventions without the use of co-design, and no intervention. A random effects meta-analysis was conducted, and the standardized mean difference (SMD) was used to report effect estimates. Quality of evidence was rated using GRADE. Results Of 16,191 studies screened, eight (N = 16,733) were included in this review. Most studies reported results favouring the effect of co-design on physical activity; however, only two studies (N = 433) could be pooled for meta-analysis resulting in a SMD of 0.28, (95% CI = -0.13 to 0.69; p = 0.19; I2 = 56%) immediately post-intervention. The GRADE quality of evidence was very low. The quantitative analysis of three studies reported improved physical function. Conclusion This review did not demonstrate that co-designed PA interventions are more effective than standard care for increasing PA in older adults; however, evidence was limited and of very low quality. Further well-designed trials are warranted to better understand the impacts of co-designed PA interventions and how to best implement them into practice. Trial registration PROSPERO registration number: CRD42022314217.